Surface Area of Lithium-Metal Electrodes Measured by Argon Adsorption. Issue 14 (1st January 2019) - Weber, Rochelle; Cheng, Ju-Hsiang; Louli, A. J.; Coon, Matthew; Hy, Sunny; Dahn, J. R.
Abstract : Rechargeable cells that rely on the stripping and plating of lithium during discharge and charge, respectively, must maintain smooth and flat lithium morphology to attain long cycle life. Higher surface area lithium metal, associated with dendrites or porous deposits, will increase the rate of reaction with liquid electrolyte, accelerate capacity loss, and decrease safety. Here we use argon BET to measure the specific surface area of lithium-metal electrodes as a function of cycle number. For "anode-free" cells with 1M LiPF6 in FEC:DEC electrolyte, the specific surface area of the lithium electrode increases by more than three times after 20 charge-discharge cycles. This measurement provides an assessment of degradation that can be linked to capacity loss and safety, which averages over the entire electrode and is therefore an excellent quantitative complement to SEM images used to look at lithium-morphology.